PD-1 N58-Glycosylation-Dependent Binding of Monoclonal Antibody Cemiplimab for Immune Checkpoint Therapy - Lu, Dan; Xu, Zepeng; Zhang, Ding; Jiang, Min; Liu, Kefang; He, Juanhua; Ma, Dongli; Ma, Xiaopeng; Tan, Shuguang; Gao, George F.; Chai, Yan (Frontiers in Immunology, 2022)
Immune checkpoint therapy (ICT) with monoclonal antibody (MAb) against programmed cell death protein 1 (PD-1) has been demonstrated to be powerful in clinical treatment for tumors. Cemiplimab is a human IgG4 antibody approved in 2018 and is the first mAb proven to be effective for locally advanced basal cell carcinoma. Here we report the crystal structure of cemiplimab and PD-1 complex and the effects of PD-1 N-glycosylation on the interactions with cemiplimab. The structure of the cemiplimab/PD-1 complex shows that cemiplimab binds to PD-1 mainly with its heavy chain, whereas the light chain serves as predominant region to compete the binding of PD-L1 to PD-1. The interaction network of cemiplimab to PD-1 is found to resemble that of camrelizumab (another PD-1 binding MAb) and the N58 glycan on the BC loop of PD-1 may be involved in the interaction with cemiplimab. The binding affinity of cemiplimab with PD-1 was found to be substantially decreased with N58 glyan deficient PD-1, whereas the PD-1/PD-L1 blocking efficiency of cemiplimab was attenuated upon binding to the N58 glycosylation deficient PD-1. These results indicate that both the binding and blocking efficacy of cemiplimab require the N58 glycosylation of PD-1. Taken together, these findings expand our understanding of the significance of PD-1 glycosylation in the interaction with cemiplimab.